2014
DOI: 10.1371/journal.pcbi.1003452
|View full text |Cite
|
Sign up to set email alerts
|

Global Patterns of Protein Domain Gain and Loss in Superkingdoms

Abstract: Domains are modules within proteins that can fold and function independently and are evolutionarily conserved. Here we compared the usage and distribution of protein domain families in the free-living proteomes of Archaea, Bacteria and Eukarya and reconstructed species phylogenies while tracing the history of domain emergence and loss in proteomes. We show that both gains and losses of domains occurred frequently during proteome evolution. The rate of domain discovery increased approximately linearly in evolut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
65
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 69 publications
(68 citation statements)
references
References 97 publications
(169 reference statements)
3
65
0
Order By: Relevance
“…It can also be a conceptual challenge to visualize the effects of protein domain gain, loss, inversions, and rearrangements in concatenation of several genes. These are well-known evolutionary processes influencing the history of molecular sequences [89] and could pose serious issues especially when primary sequence identity between proteins is very low, as could be the case when comparing distantly related taxa over long evolutionary timespans. Simulations have also shown that concatenated gene sets can lead to inconsistencies and produce misleading trees with high BS values [35], in addition to known issues of heterotachy [36].…”
Section: Technical Issues Related To Taxon and Character Sampling mentioning
confidence: 99%
“…It can also be a conceptual challenge to visualize the effects of protein domain gain, loss, inversions, and rearrangements in concatenation of several genes. These are well-known evolutionary processes influencing the history of molecular sequences [89] and could pose serious issues especially when primary sequence identity between proteins is very low, as could be the case when comparing distantly related taxa over long evolutionary timespans. Simulations have also shown that concatenated gene sets can lead to inconsistencies and produce misleading trees with high BS values [35], in addition to known issues of heterotachy [36].…”
Section: Technical Issues Related To Taxon and Character Sampling mentioning
confidence: 99%
“…The phylogenetic distribution of the different domain types as well as of the domain pairs formed by them, showed equally large variations among the extant lineages and taxa (Table S7), which could reflect adaptations to the specific organismal biology. Higher eukaryotes are known to exhibit elevated rates of domain rearrangements and duplications, mainly as a result of their larger genomes and more complex biology [30]. In our dataset, the Arthropoda and Cephalochordata clades exhibited the highest numbers in unique domain types (58 and 25, respectively) and consequently unique domain pairs (98 and 44, respectively) in modular CBM14‐containing proteins.…”
Section: Resultsmentioning
confidence: 85%
“…These low levels and perhaps transitory increments of oxygen could have originated from biotic or abiotic reactions, such as enzymatic ROS-detoxifying reactions or water UV photolysis (Martin and Sousa, 2016). It is probable that during those “oxygen whiffs,” many proteins would be the object of selection pressure to survive in oxygen that could force them to lose or gain new features such as protein domains (Nasir et al, 2014) or physiological activities. In addition, the ancient hot environment of the Archaean eon could helped to accelerate the evolutionary rate of change of these proteins, as postulated to be occurring in current extreme environments (Li et al, 2014).…”
Section: Resultsmentioning
confidence: 99%